Visible light-harvesting trans bis(alkylphosphine) platinum(II)-alkynyl complexes showing long-lived triplet excited states as triplet photosensitizers for triplet-triplet annihilation upconversion - DRAPER, SYLVIA (My University, 2013)
Symmetric and asymmetric linear trans-bis(tributylphosphine) Pt(II) bis(acetylide) complexes with functionalized aryl alkynyl ligands (coumarin, naphthalimide and phenyl acetylides) were prepared, which show enhanced absorption in the visible region (molar absorption coefficients up to 76 800 M?1 cm?1 at 459 nm) and long-lived triplet excited states (up to 139.9 ?s). At room temperature, the naphthalimide acetylide?phenyl acetylide complex (Pt-4) shows dual emission (fluorescence?phosphorescence), whereas other complexes show only fluorescence emission. The triplet excited states of the complexes were studied with nanosecond time-resolved transient difference absorption spectroscopy and DFT calculations on the spin density surface. The complexes were used as triplet photosensitizers for ratiometric O2 sensing, as well as triplet?triplet annihilation (TTA) upconversion (upconversion quantum yield up to 27.2%). The TTA upconversion of the complexes requires triplet acceptors with different T1 state energy levels and was studied with nanosecond time-resolved emission spectroscopy. Our results are useful for designing new Pt(II) complexes that show strong absorption of visible light and long-lived triplet excited states, as well as for the application of these complexes as triplet photosensitizers for O2 sensing, photocatalysis and TTA upconversion.
PUBLISHED
Keywords: Chemistry; Nanoscience & Materials; Smart & Sustainable Planet